Statistical Software Use in Canadian University Courses: Current Trends and Future Directions. (July 2019) - Davidson, Heather; Jabbari, Yasaman; Patton, Heather; O'Hagan, Fergal; Peters, Kevin; Cribbie, Robert
Two controversial topics related to the teaching of statistics to psychology students are (a) when to introduce statistical software and (b) which statistical software package to use. The current research looked at the use of statistical software in statistics classes from every university with a psychology program in Canada. Researchers collected data from 321 statistics courses offered to psychology students at 65 Canadian universities and coded the type of statistical software used (if any) in each course. Results show that slightly more than half of all universities introduce software at the introductory level. Point-and-click software is most popular, particularly SPSS. There is a considerable amount of variability in when and which software is introduced to students. Departments can use these data to inform their own practices.